A study of patch testing in subjects with hand eczema of different occupational groups - Bhachech, Harshit T.; Jaiswal, Chandra Shekhar R. P.; Mehta, Hita Hemant (International Journal Of Community Medicine And Public Health, 2016)
Background: Hand dermatitis is a common dermatological disorder in different occupational groups. Patch Testing serves as an important tool for identifying allergens responsible for contact dermatitis. Methods: A study of patch testing was conducted in patients of hand eczema of different occupational groups with aim to identify allergens for particular occupational groups. Study was conducted as an observational study of patch testing in patients of hand eczema who attended skin OPD in our hospital in one year duration. After detailed history and complete examination, patch testing was done by Indian Standard Series in 45 Patients of hand dermatitis. There were eight farmers, eight masons, five housewives, four diamond workers, eight miscellaneous labourers and 12 patients of varied non-specific occupations. Grading was done using ICDRG criteria at 48 and 72 hrs. Results: Among 45 patients, 35 were male and 10 female. Positive patch test was seen in 62.2% of patients with parthenium being the most common allergen (27%), followed by potassium dichromate (18.2%). There were extreme positive results in five, strong positive in ten and weak positive in rest positive results. 87.5 % occupation-allergen co-relation was seen in farmers followed by 50 % among masons. Only two patients showed variation in reading between 48 hr and 72 hr. Conclusions: Our study showed good correlation between occupation and positive patch test especially among farmers and masons. Many other non-specific allergens were also found positive and exposure to those can be prevented to avoid hand eczema in different occupational groups.